Recent advances in marine biotechnology (Science Publishers, 2003)
Genetic evaluation of brood stock for aquaculture of Red Sea bream by DNA markers; application of biotechnology to enhance growth of salmonids and other fish; potential application of recombinant hormones and growth factors in fish culture; the molecular genetics of transgenic fish; the application of gene manipulation to aquaculture; evolution of endocrine growth regulation - the insulin-like growth factors (IGFs), their regulatory binding proteins (IGFBPs) and IGF receptors in fishes and other ectothermic vertebrates; gene transfer in marine finfish and shellfish.